How do fisher responses to macroalgal overgrowth influence the resilience of coral reefs?. Issue Volume 67:Issue S1(2022)Special issue (30th August 2021) - Rassweiler, Andrew; Miller, Scott D.; Holbrook, Sally J.; Lauer, Matthew; Strother, Mark A.; Lester, Sarah E.; Adam, Thomas C.; Wencélius, Jean; Schmitt, Russell J.
Abstract: Many coral reefs have shifted from coral‐ to macroalgae‐dominated community states, heightening the need to understand resilience of coral communities. Fishing on herbivores often reduces resilience of the coral state, as lower herbivory fosters macroalgal establishment. Despite the acknowledged importance of fishing, relatively little attention has been paid to how fishers change their behavior as macroalgae overgrow reefs, or how the resulting dynamic feedbacks might affect resilience. We address these questions in Moorea, French Polynesia, where local fishers target herbivorous fishes and where shifts to algal dominance have occurred on some lagoon reefs. We quantified fisher preferences for reef habitats where they target various taxa. For the two most ecologically important taxa of herbivores targeted in the fishery, parrotfish (Scaridae) and unicornfish ( Naso ), fishers preferred to harvest from locations with less macroalgae. We incorporated these habitat preferences into a spatially explicit social–ecological model of reef dynamics to explore consequences of changes in fishing behavior for resilience of the coral state, particularly following disturbance. Fishing that targets low‐macroalgae locations typically generates resilience by facilitating local recovery of herbivores and thus of coral in the less‐targeted macroalgae‐dominated patches. However, the resulting movement of fishers across the seascape can sometimes create fragility; if coral loss is widespread, avoidance of macroalgae concentrates fishing in patches having the highest coral cover, resulting in loss of coral via reduced herbivory. Our results emphasize that resilience and coral‐macroalgae regime shifts cannot be understood without considering humans as a dynamic part of the system.